A methodology for the development of innovation clusters: application in the healthcare sector. (1st January 2014) - Zimmer, Benjamin; Stal-Le Cardinal, Julie; Yannou, Bernard; Le Cardinal, Gilles; Piette, François; Boly, Vincent
For more than ten years, the French State and administrative regions have pursued economic development policies that stimulate all forms of innovation and encourage strategic market alliances of the economic stakeholders of a region. These 'cluster' policies aim to create ecosystems that are conducive to innovation and promote the emergence of collaborative organisations. Among these innovation clusters, we are concerned with those in the healthcare field pertaining to ageing and autonomy. Business models and action plans for these collaborative organisations are neither easy to define nor easy to stabilise and reinforce, because of the diversity of stakeholders with multiple expectations involved. This paper presents an application of the FAcT-Mirror method in the Sol'iage (http://www.soliage.com/english-version/ ) innovation cluster during its development stage. We demonstrate that the FAcT-Mirror method is particularly efficient and effective during the process of transformation from the emerging stage (stage of intention) to the development stage (stage of action) for a healthcare cluster to collectively produce common tools (definitions, strategy, working groups, and action plans).